THE PRACTICAL SIGNIFICANCE OF STUDENTS' VIEWS OF FAMILY LIFE - Dzhukhanova Nakhida Khayotjonovna (Bright Mind Publishing, 2025)
This article identifies that psychological readiness for marriage is a complex personal formation, with its main components being: marital values, marriage motivation, the concept of marital hierarchy, marital relationships and expectations, and the idea of marital relations. It was determined that each component has its own structural composition.
Keywords: Social heterogeneity, neurosis, psychasthenia, hysteria, sexual impotence, economic vulnerability.